The Darkened Room. Women, Power and Spiritualism in Late Victorian England - Cook, Ramsay (Labour / Le Travail, 1991)
The article reviews the book, "The Darkened Room: Women, Power and Spiritualism in Late Victorian England," by Alex Owen.
Keywords: BOOKS -- Reviews; DARKENED Room: Women, Power & Spiritualism in Late Victorian England, The (Book); Nonfiction; OWEN, Alex; SPIRITUALISM